Survey Kepuasan Member Fitness Terhadap Pelayanan yang Diberikan Brother Gym Kota Palembang - rudi hermawan; Maya Kurnia; Mutiara Fajar (Jurnal Speed (Sport, Physical Education, Empowerment), 2021)
This study aims to determine the level of satisfaction of Fitness Brother Gym Members in Palembang City. This research is a quantitative descriptive research with the type of survey research. Research data obtained through questionnaires and documentation. Data analysis used questionnaire data analysis techniques by looking for the relative frequency of the percentage. The results showed that the satisfaction of fitness members with the services provided at Brother Gym in Palembang was included in the satisfactory category of 24 people with a percentage of 80% and followed by a very satisfactory category of 6 people with a percentage of 20%. This situation shows that the services provided by Brother Gym in Palembang are good and in accordance with the needs of fitness members. Especially in the assurance and empathy categories, namely: the company's attention to members, understanding the needs of members, friendliness, and assurance of safety and security. Keywords: Service Survey, Service